Photochemical transformation of a cellulose biosynthesis inhibitor into phytoene desaturase inhibitors. (15th October 2021) - Wakeham, Matthew C.L.; Lim, Zelong; Lindell, Stephen D.; Laber, Bernd; Hain, Rüdiger; Jeschke, Peter; Hey, Daniel
Graphical abstract: Abstract: Mode of action studies showed that 5-methyl-N, N-bis[6-(trifluoromethyl)pyridin-3-yl]pyridin-2-amine (4 ), a representative from a new class of herbicidal tris-pyridyl amines, is an inhibitor of cellulose biosynthesis (CB). The compound undergoes an oxidative photocyclization, when exposed to UV-B light (300–340 nm) in the presence of oxygen, to give a new class of herbicidal pyrrolodipyridines. These compounds are potent inhibitors of the herbicide target enzyme phytoene desaturase and no longer inhibit CB.